A design thinking approach to evaluating interprofessional education. Issue 3 (3rd May 2016) - Cahn, Peter S.; Bzowyckyj, Andrew; Collins, Lauren; Dow, Alan; Goodell, Kristen; Johnson, Alex F.; Klocko, David; Knab, Mary; Parker, Kathryn; Reeves, Scott; Zierler, Brenda K.
ABSTRACT: The complex challenge of evaluating the impact of interprofessional education (IPE) on patient and community health outcomes is well documented. Recently, at the Radcliffe Institute for Advanced Study in the United States, leaders in health professions education met to help generate a direction for future IPE evaluation research. Participants followed the stages of design thinking, a process for human-centred problem solving, to reach consensus on recommendations. The group concluded that future studies should focus on measuring an intermediate step between learning activities and patient outcomes. Specifically, knowing how IPE-prepared students and preceptors influence the organisational culture of a clinical site as well as how the culture of clinical sites influences learners' attitudes about collaborative practice will demonstrate the value of educational interventions. With a mixed methods approach and an appreciation for context, researchers will be able to identify the factors that foster effective collaborative practice and, by extension, promote patient-centred care.